The Strategic Environment of the Aviation Industry in UAE: A Case Study on Etihad Airways - Bose, Indranil (IIUM Journal of Case Studies in Management, 2018)
UAE is one of the most dynamic aviation markets in the world, with three world class airports, including the busiest airport of the world; millions of passengers travelling through these airports and many highly competitive local and international airlines operating from here. Etihad Airways is one of the frontrunners among them. The intense competition has forced all the airlines operating from UAE to continuously become more innovative and best in service delivery. Etihad is also encountering some challenges since its inception and still has emerged as one of the most profitable and fastest growing airlines in the world. The present paper has taken Etihad as a case study and analyzed the same with relevant strategic model such as PESTLE model. Different recommendations have been developed at the end of the discussion and those can be further used in future.